How to be a millennial parent a textual analysis on microcelebrities and sharenting practices online - Gonsalves, Angela Denise, 1997-; Tolentino, Daphne Tatiana; University of the Philippines Diliman. College of Mass Communication (Quezon City College of Mass Communication, University of the Philippines Diliman, 2018)
This study aims to explore how sharenting is becoming an increasingly normal practice among young, Filipino parents by examining the sharenting practices of their contemporary celebrity sharents as displayed on the image-sharing platform, Instagram. In 2014, Blum-Ross and Livingstone introduced the term "sharenting", or the act of sharing information about their children by parents on blogs and social networking sites which, through their posting, has allowed the launch of these children into stardom. In this study, I will analyze the photos and videos of children posted on Instagram accounts by their very own celebrity parents. By posting these photos and videos on Instagram, these micro-celebrity parents are able to accumulate symbolic capital, which transforms them into cultural procedures that legitimize the practice of sharenting in Filipino families today. Drawing from Bourdieu's Theory of Practice and Symbolic Violence, this study will specifically look at the different sharenting practices of Filipino celebrity sharents with children ages 0-5 years old. I will conduct interviews with non-celebrity sharents in order to come up with a side by side analysis that reveals which practices between the two are similar with each other, and how Bourdieu's concept of symbolic violence plays a role in legitimizing the practice.
Vita.
Thesis (A. B. Broadcast Communication)--University of the Philippines Diliman
Includes bibliographical references.
Keywords: Internet and children -- Safety measure; Parent and child; Internet and children -- Social aspects